Broken trust in the supply chain: A qualitative study of product authentication failures, procedural fragmentation, and inventory consequences in Ghana's Upper West Region public hospitals - Cyril Kutina; Clement Nangpiire; Abdul-Aziz Dawdi (International Journal of Business and Management (IJBM), 2026)
Effective medical supply chain management is a critical component of health systems, particularly for patient safety in low‑ and middle‑income countries (LMICs). Ghana's public hospitals face long‑standing challenges in product authentication, transparency, and inventory control, especially in resource‑constrained regions, driven by weak infrastructure, disjointed accountability, and limited digital connectivity. This study examined the lived experiences of frontline healthcare personnel managing medical supply chains in Ghana's Upper West Region, focusing on how vulnerabilities in product integrity, procedural inefficiency, and inventory mismanagement jointly affect patient safety and service delivery. A qualitative descriptive design was used, with semi‑structured, face‑to‑face interviews conducted across three public hospitals, one referral hospital and two district/municipal hospitals in the Upper West Region between January and April 2026. Data were analyzed using Braun and Clarke's (2022) six‑step thematic framework in MAXQDA 26.0. Thematic saturation was reached after the 21st interview. Twenty‑one participants were interviewed, yielding three major themes: (1) Vulnerabilities in Product Integrity and Safety — no participant reported a reliable authentication method, forcing reliance on visual inspection and supplier trust; (2) Procedural and Logistical Inefficiencies, fragmented accountability, manual documentation, and mandatory central sourcing created information gaps at every handoff; and (3) Inventory Control Consequences, simultaneous shortages and overstocking eroded patient trust, triggered unplanned referrals, and disrupted surgical scheduling. These findings offer a diagnostic basis for designing sequenced, low‑cost technology interventions suited to rural LMIC hospital settings. The study contributes qualitative depth to a literature dominated by quantitative stock‑out research and offers practical, context‑sensitive recommendations, including threshold‑based procurement rules, low‑cost cold‑chain indicators, and standardized receiving protocols, for strengthening supply chain integrity in resource‑constrained health systems.